A dual-route perspective on poor reading in a regular orthography: An fMRI study - Wimmer, Heinz (Masson, 2010)
This study examined functional brain abnormalities in dyslexic German readers who – due to the regularity of German in the reading direction – do not exhibit the reading accuracy problem of English dyslexic readers, but suffer primarily from a reading speed problem. The in-scanner task required phonological lexical decisions (i.e., Does xxx sound like an existing word?) and presented familiar and unfamiliar letter strings of existing phonological words (e.g., Taxi-Taksi) together with nonwords (e.g., Tazi). Dyslexic readers exhibited the same response latency pattern (words < pseudohomophones < nonwords) as nonimpaired readers, but latencies to all item types were much prolonged. The imaging results were suggestive for a different neural organization of reading processes in dyslexic readers. Specifically, dyslexic readers, in response to lexical route processes, exhibited underactivation in a left ventral occipitotemporal (OT) region which presumably is engaged by visual-orthographic whole word recognition. This region was also insensitive to the increased visual-orthographic processing demands of the sublexical route. Reduced engagement in response to sublexical route processes was also found in a left inferior parietal region, presumably engaged by attentional processes, and in a left inferior frontal region, presumably engaged by phonological processes. In contrast to this reduced engagement of the optimal left hemisphere reading network (ventral OT, inferior parietal, inferior frontal), our dyslexic readers exhibited increased engagement of visual occipital regions and of regions presumably engaged by silent articulatory processes (premotor/motor cortex and subcortical caudate and putamen).